2007
DOI: 10.1038/oby.2007.588
|View full text |Cite
|
Sign up to set email alerts
|

BMI and Waist Circumference in Predicting Cardiovascular Risk Factor Clustering in Chinese Adolescents

Abstract: Research Methods and Procedures:A total of 2102 Hong Kong Chinese 12 to 19 years of age were recruited. Participants were considered to have clustering of risk factors if at least three of the following risk factors were present: 1) high-density lipoprotein cholesterol (HDL-C) Յ1.03 mM, 2) low-density lipoprotein cholesterol (LDL-C) Ն2.6 mM, 3) triglyceride (TG) Ն1.24 mM, 4) fasting plasma glucose (FPG) Ն6.1 mM, and 5) age-, sex-, and height-adjusted systolic or diastolic blood pressure (BP) Ն 90th percentile.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 37 publications
(38 reference statements)
6
56
2
Order By: Relevance
“…19 The local percentile standards were based on the latest local population survey. 20 Subjects were considered to have clustering of cardiovascular risk factors according to the modified criteria used in the Third National Health and Nutrition Examination Survey 21 : three or more of the following risk factors HDL-C 1.03 mmol/L, LDL-C ! 2.6 mmol/L, TG !…”
Section: Discussionmentioning
confidence: 99%
“…19 The local percentile standards were based on the latest local population survey. 20 Subjects were considered to have clustering of cardiovascular risk factors according to the modified criteria used in the Third National Health and Nutrition Examination Survey 21 : three or more of the following risk factors HDL-C 1.03 mmol/L, LDL-C ! 2.6 mmol/L, TG !…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies with a longitudinal design are needed to confirm our findings. 41 in their study with children and adolescents aged 10-15 years observed that BMI and triceps skinfold thickness accurately predicted obesity (AUCs ranged 44 . Differences between studies may be due to methodological differences in data collection or even in data preparation (i.e.…”
mentioning
confidence: 96%
“…19,20 In brief, 53 schools were randomly selected from 477 secondary schools in Hong Kong using a computer-generated coding system. Of these 53 schools, 14 schools participated in the survey with consent from school principals.…”
Section: Subjectsmentioning
confidence: 99%
“…19,20 Fasting blood samples were assayed for fasting plasma glucose (FPG), fasting insulin (FINS), lipids, triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and calculated low-density lipoprotein cholesterol (LDL-C). Sera were also assayed for IGF-I and IGFBP-3 by an automated chemiluminescent assay system (IMMULITE 2000; Diagnostic Products Corp., Los Angeles, CA, USA).…”
Section: Clinical and Laboratory Assessmentsmentioning
confidence: 99%